QTL mapping and transcriptome analysis of sugar content during fruit ripening of Pyrus pyrifolia - Jiang, Shuang; Li, Shuigen; Luo, Jun; Wang, Xiaoqing; Shi, Chunhui (Frontiers in Plant Science, 2023)
Sugar content is an important trait of fruits. The genetic background of fruits can affect their sugar content in different cultivars. The quantitative trait loci and genes related to sugar content during fruit ripening remain unclear. In this study, we performed quantitative trait locus (QTL) mapping of sugar content. Two QTLs (qSugar-LG6-Chr7 and qSugar-LG12-Chr3) were identified based on their total sugar contents. A total of 577 and 519 genes were annotated around these two QTL loci. The contents of fructose, sorbitol, glucose, and sucrose were measured at six time points in four cultivars before fruit maturation, including two sweet cultivars (‘Zaoshengxinshui’ and ‘ZQ65’) and two general cultivars (‘Qiushui’ and ‘ZQ82’). In sweet cultivars, sucrose and fructose accumulate substantially, and sorbitol content decreases significantly during fruit ripening. A transcriptome analysis identified 125 upregulated and 222 downregulated differentially expressed genes (DEGs) in sweet cultivars. Two sucrose transport genes (PpSUT, LOC103964096, and LOC103940043) were negatively correlated with sugar content. A weighted gene co-expression network analysis analysis showed that two genes, sorbitol dehydrogenase (PpSDH, LOC103960512 and LOC103960513), around the locus of qSugar-LG6-Chr7 were negatively co-expressed with the total sugar content, which was downregulated in the sweet cultivars. PpSDH and PpSUT may play important roles in regulating sugar content during pear ripening. Transcriptome analysis also revealed that some DEGs were related to sugars (PpS6PDH and ATP-PpPFK), hormones (PpARG7), and transcription factors (PpEMB1444, PpCYP734A1, PpWRKY50). In conclusion, this study provides new insights into the molecular mechanisms associated with sugar content in the fruit ripening of Pyrus pyrifolia.